Transperitoneal laparoscopic retrievement of a migrated prosthetic head after total hip arthroplasty: a case report - Ciciriello, Simone; Gerosa, Martino; Ghezzi, Riccardo; Sogni, Angelo; Incalza, Ferdinando; Guttadauro, Angelo; Maggioni, Dario; Mari, Giulio (Frontiers in Surgery, 2023)
The migration of a prosthetic head during total hip arthroplasty (THA) is a rare complication. Few cases are described in literature, offering different solutions and surgical approaches for the prosthetic head retrievement. Here we present a case of successful laparoscopic trans-peritoneal retrieval of a prosthetic head migrated above the right iliac vein after THA with postero-lateral approach.